Survey Paper on Automatic Speaker Recognition Systems (International Journal of Engineering and Computer Science, 2017)
In this paper we present an overview of approaches for Speaker recognition. Speaker recognition is the process of automatically recognizing a person on the basis of individual information included in speech signals. Voiceprint Recognition System also known as a Speaker Recognition System (SRS) is the best-known commercialized forms of voice Biometric. The Speech is most essential & primary mode of Communication among of human being. In this paper we are focus on speaker identification and various feature extraction methods used for speaker identification system.